Effects of buprofezin and imidacloprid on the functional response of Eretmocerus mundus Mercet - Fariba Sohrabi; Parviz Shishehbor; Moosa Saber; Mohammad Said Mosaddegh (Plant Protection Science, 2014)
Eretmocerus mundus Mercet is one of the key natural enemies of Bemisia tabaci (Gennadius). In this study, the sublethal effects of LC25 of imidacloprid and field-recommended concentration of buprofezin on the functional response of E. mundus to different densities of second instar B. tabaci nymphs were evaluated. The results revealed a type III functional response in the control and imidacloprid treatment. The type III functional response was altered into a type II by buprofezin. Although imidacloprid did not alter the type of functional response of E. mundus compared to the control, it negatively affected the handling time and maximum attack rate of the parasitoid. Therefore, the use of this insecticide should be evaluated carefully in IPM programs.